Holocene dynamics of tree taxa populations in Italy - Magri, Donatella; Agrillo, Emiliano; Di Rita, Federico; Furlanetto, Giulia; Pini, Roberta; Ravazzi, Cesare; Spada, Francesco (Review of Palaeobotany and Palynology, 2014)
The Holocene distribution of nine tree taxa (Picea, Abies, Betula, Fagus, Carpinus betulus, Corylus, deciduous and evergreen Quercus, and Olea) in Italy is visually shown by pollen maps. A hundred pollen sites were selected, percentageswere derived fromthe original pollen counts or digitized frompublished diagrams, and represented on maps in subsequent time windows at 1000-year intervals. The pollen maps depict the Holocene history of Italian forest cover as a complex puzzle influenced by very diverse climate, physiography, edaphic and ecological processes, and a long history of human activity. A reasonably goodmatch between the abundance and distribution of pollen data during the last thousand years and the current tree species distribution in Italy indicates that the Holocene pollen maps may represent a fundamental basis for a better understanding of the modern vegetation patterns, often showing discontinuous ranges and complex distributions. Although clear latitudinal gradientswere not detected, regions characterized by high precipitation values hosted dense forest cover since the Holocene onset, while areas with arid climate experienced a delayed increase in trees and a faster decrease during the last four millennia. Fagus, C. betulus and Picea showdisplacement in their distribution inItaly in the course of theHolocene.Other taxa, likedeciduous and evergreen Quercus, and Betula have always occupied the same locations during the Holocene, but show changes in abundance. Abies had a broken distribution in Italy throughout the postglacial. Its populations are currently found within the regions they occupied at the onset of the Holocene. The importance of considering all the available records in their geographical context to reconstruct complex vegetational patterns is discussed.
Keywords: Database; Holocene; Italy; Pollen map; Woody taxon

Towards the harmonization between National Forest Inventory and Forest Condition Monitoring. Consistency of plot allocation and effect of tree selection methods on sample statistics in Italy - Gasparini, Patrizia; Di Cosmo, Lucio; Cenni, Enrico; Pompei, Enrico; Ferretti, Marco (ENVIRONMENTAL MONITORING AND ASSESSMENT, 2013)
In the frame of a process aiming at harmonizing National Forest Inventory (NFI) and ICP Forests Level I Forest Condition Monitoring (FCM) in Italy, we investigated (a) the long-term consistency between FCM sample points (a subsample of the first NFI, 1985, NFI_1) and recent forest area estimates (after the second NFI, 2005, NFI_2) and (b) the effect of tree selection method (tree-based or plot-based) on sample composition and defoliation statistics. The two investigations were carried out on 261 and 252 FCM sites, respectively. Results show that some individual forest categories (larch and stone pine, Norway spruce, other coniferous, beech, temperate oaks and cork oak forests) are over-represented and others (hornbeam and hophornbeam, other deciduous broadleaved and holm oak forests) are under-represented in the FCM sample. This is probably due to a change in forest cover, which has increased by 1,559,200 ha from 1985 to 2005. In case of shift from a tree-based to a plot-based selection method, 3,130 (46.7 %) of the original 6,703 sample trees will be abandoned, and 1,473 new trees will be selected. The balance between exclusion of former sample trees and inclusion of new ones will be particularly unfavourable for conifers (with only 16.4 % of excluded trees replaced by new ones) and less for deciduous broadleaves (with 63.5 % of excluded trees replaced). The total number of tree species surveyed will not be impacted, while the number of trees per species will, and the resulting (plot-based) sample composition will have a much larger frequency of deciduous broadleaved trees. The newly selected trees have-in general-smaller diameter at breast height (DBH) and defoliation scores. Given the larger rate of turnover, the deciduous broadleaved part of the sample will be more impacted. Our results suggest that both a revision of FCM network to account for forest area change and a plot-based approach to permit statistical inference and avoid bias in the tree sample composition in terms of DBH (and likely age and structure) are desirable in Italy. As the adoption of a plot-based approach will keep a large share of the trees formerly selected, direct tree-by-tree comparison will remain possible, thus limiting the impact on the time series comparability. In addition, the plot-based design will favour the integration with NFI_2.
The following values have no corresponding Zotero field: pub-location: VAN GODEWIJCKSTRAAT 30, 3311 GZ DORDRECHT, NETHERLANDS publisher: SPRINGER
Keywords: Forest condition monitoring; Forest inventory; Italy; Plot allocation; Sample statistics; Tree selection methods

Classifying and Mapping Potential Distribution of Forest Types Using a Finite Mixture Model - Attorre, Fabio; Francesconi, Fabio; Sanctis, Michele; Alfò, Marco; Martella, Francesca; Valenti, Roberto; Vitale, Marcello (Folia Geobotanica, 2012)
The present paper presents the application of a finite mixture model (FMM) to analyze spatially explicit data on forest composition and environmental variables to produce a high-resolution map of their current potential distribution. FMM provides a convenient yet formal setting for model-based clustering. Within this framework, forest data are assumed to come from an underlying FMM, where each mixture component corresponds to a cluster and each cluster is characterized by a different composition of tree species. An important extension of this model is based on including a set of covariates to predict class membership. These covariates can be climatic and topographical parameters as well as geographical coordinates and the class membership of neighbouring plots. FMM was applied to a national forest inventory of Italy consisting of 6,714 plots with a measure of abundance for 27 tree species. In this way, a map of potential forest types was produced. The limitations and usefulness of the proposed modelling approach were analyzed and discussed, comparing the results with an independently derived expert map
Keywords: Classification; Finite Mixture Model; forest types; Italy; Potential distribution

Impacts of changing climate and land use on vegetation dynamics in a Mediterranean ecosystem: insights from paleoecology and dynamic modeling - Henne, Paul D.; Elkin, Ché; Colombaroli, Daniele; Samartin, Stéphanie; Bugmann, Harald; Heiri, Oliver; Tinner, Willy (Landscape Ecology, 2012)
Forests near the Mediterranean coast have been shaped by millennia of human disturbance. Consequently, ecological studies relying on modern observations or historical records may have difﬁculty assessing natural vegetation dynamics under current and future climate. We combined a sedimentary pollen record from Lago di Massacciucoli, Tuscany, Italy with simulations from the LANDCLIM dynamic vegetation model to determine what vegetation preceded intense human disturbance, how past changes in vegetation relate to ﬁre and browsing, and the potential of an extinct vegetation type under present climate. We simulated vegetation dynamics near Lago di Massaciucoli for the last 7,000 years using a local chironomid-inferred temperature reconstruction with combinations of three ﬁre regimes (small infrequent, large infrequent, small frequent) and three browsing intensities (no browsing, light browsing, and moderate browsing), and compared model output to pollen data. Simulations with low disturbance support polleninferred evidence for a mixed forest dominated by Quercus ilex (a Mediterranean species) and Abies alba (a montane species). Whereas pollen data record the collapse of A. alba after 6000 cal yr BP, simulated populations expanded with declining summer temperatures during the late Holocene. Simulations with increased ﬁre and browsing are consistent with evidence for expansion by deciduous species after A. alba collapsed. According to our combined paleoenvironmental and modeling evidence, mixed Q. ilex and A. alba forests remain possible with current climate and limited disturbance, and provide a viable management objective for ecosystems near the Mediterranean coast and in regions that are expected to experience a mediterranean-type climate in the future.
Keywords: Abies alba; Chironomids; Fire ecology; Holocene; Italy; Landscape model; mediterranean forest; Neolithic; pollen; Quercus ilex

The likely impact of climate change on the biodiversity of Italian forests - Borghetti, M.; La Mantia, T.; Menozzi, P.; Piotti, a (Forest@ - Rivista di Selvicoltura ed Ecologia Forestale, 2012)
Keywords: 2012; 245-250; 9; Adaptation; biodiversità delle foreste italiane; Biodiversity; borghetti m; citation; climate change; climatico sulla; contents; FOREST; http; impact; it; Italy; la mantia t; menozzi p; online 2012-11-19; piotti a; probabili impatti del cambiamento; sisef; url; www

Traditional plant use in the National Park of Cilento and Vallo di Diano, Campania, Southern, Italy. - Di Novella, Riccardo; Di Novella, Nicola; De Martino, Laura; Mancini, Emilia; De Feo, Vincenzo (Journal of ethnopharmacology, 2012)
AIM OF STUDY: This paper reports an ethobotanical survey of the traditional uses of medicinal and useful plants in an area of the National Park of Cilento and Vallo di Diano, Campania, Southern Italy. MATERIALS AND METHODS: This study conducted between 2009 and 2011, gathered information on the medicinal plants traditionally used in Southern Italy (Campania Region). In all, we interviewed 70 key informants, whose age ranged between 50 and 85 years. This people belonged to families which had strong links with traditional activities of the area. RESULTS: The research resulted to the identification of 192 plants belonging to 64 families. Among the species reported, 86 are used in human medicine, 15 in veterinary medicine, 69 as human foods, 18 as animal feed, 61 for domestic and 8 for agricultural uses. CONCLUSION: A survey of the available literature on Southern Italy ethnobotany reveals that some species have been never reported and about 10% of cited uses are new. Data obtained show that in the studied area the folk use of plants is alive and still derives from daily practice.
The following values have no corresponding Zotero field: publisher: Elsevier accession-num: 23159473
Keywords: Agriculture; Agriculture: methods; Animal Feed; Animal Feed: utilization; Data Collection; Ethnobotany; Ethnobotany: methods; Ethnobotany: statistics & numerical data; Ethnomedicine; Food; Humans; Italy; Medicinal; Medicine; National Park of Cilento and Vallo di Diano; plant traditional uses; Plants; Traditional; Traditional: utilization; Veterinary medicine; Veterinary Medicine: methods

Unravelling Soil Fungal Communities from Different Mediterranean Land-Use Backgrounds - Orgiazzi, Alberto; Lumini, Erica; Nilsson, R Henrik; Girlanda, Mariangela; Vizzini, Alfredo; Bonfante, Paola; Bianciotto, Valeria (PLoS ONE, 2012)
Background Fungi strongly influence ecosystem structure and functioning, playing a key role in many ecological services as decomposers, plant mutualists and pathogens. The Mediterranean area is a biodiversity hotspot that is increasingly threatened by intense land use. Therefore, to achieve a balance between conservation and human development, a better understanding of the impact of land use on the underlying fungal communities is needed. Methodology/Principal Findings We used parallel pyrosequencing of the nuclear ribosomal ITS regions to characterize the fungal communities in five soils subjected to different anthropogenic impact in a typical Mediterranean landscape: a natural cork-oak forest, a pasture, a managed meadow, and two vineyards. Marked differences in the distribution of taxon assemblages among the different sites and communities were found. Data analyses consistently indicated a sharp distinction of the fungal community of the cork oak forest soil from those described in the other soils. Each soil showed features of the fungal assemblages retrieved which can be easily related to the above-ground settings: ectomycorrhizal phylotypes were numerous in natural sites covered by trees, but were nearly completely missing from the anthropogenic and grass-covered sites; similarly, coprophilous fungi were common in grazed sites. Conclusions/Significance Data suggest that investigation on the below-ground fungal community may provide useful elements on the above-ground features such as vegetation coverage and agronomic procedures, allowing to assess the cost of anthropogenic land use to hidden diversity in soil. Datasets provided in this study may contribute to future searches for fungal bio-indicators as biodiversity markers of a specific site or a land-use degree.
Keywords: air pollution; ecosystem services; ecosystems; Forests; Grazing Lands (citation); Italy; land use; Micro Organisms; Soil Capability

Biodiversity of wood-decay fungi in Italy - Saitta, A.; Bernicchia, A.; Gorjón, S. P.; Altobelli, E.; Granito, V. M.; Losi, C.; Lunghini, D.; Maggi, O.; Medardi, G.; Padovan, F.; Pecoraro, L.; Vizzini, A.; et al. (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2011)
Abstract Current knowledge about Italian wood-decay fungi (Basidiomycota and Ascomycota) is surveyed: 1582 taxa belonging to Ascomycota (341) and Basidiomycota (1241) have been reported, including 23 species new to science of Basidiomycota described from Italy within the last five years. Evaluating diversity of wood-decay fungi can provide a more accurate estimation of species richness for fungi which are an important functional component of ecosystems. Aphyllophoroid and Ascomycota species play an important role in habitat conservation and management. Sardinia, Sicily, the Alps and the Apennines are ?hot spots? for wood-decay Basidiomycota in Italy.
doi: 10.1080/11263504.2011.633114doi: 10.1080/11263504.2011.633114The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: Ascomycota; Basidiomycota; Biodiversity; Italy; wood-decay fungi

Prospects of barcoding the Italian wild dendroflora: oaks reveal severe limitations to tracking species identity. - Piredda, Roberta; Simeone, Marco C; Attimonelli, Marcella; BELLAROSA, Rosanna; Schirone, Bartolomeo (Molecular ecology resources, 2011)
DNA barcoding may be particularly important in influencing ecology, economic issues, and the fundamental crisis facing biodiversity as a standardized, species-level identification tool for taxonomy assessment. Trees play important roles in the conservation of many land ecosystems, the wood trade, and the definition of biogeographical processes; nevertheless, peculiar biological, evolutionary and taxonomical features will probably constitute an intriguing challenge to barcoders. We examined whether four marker regions (trnh-psba, rbcL, rpoc1, matK) proposed by the Consortium for the Barcode of Life (CBOL) matched species taxonomy in a preliminary tree biodiversity survey of Italian forested land. Our objective was to provide a test of future in situ applications of DNA barcodes by evaluating the efficacy of species discrimination under the criteria of uniformity of methods and natural co-occurrence of the species in the main forest ecosystems. Fifty-two species were included in a floristic study. We obtained 73% total discrimination success, with trnH-psbA as the best performing marker and oaks as the least responsive plants to the markers used. A further taxon-based study of Quercus (thirty specimens, 12 species) revealed that this genus is refractory to barcoding (0% discrimination success), a probable consequence of low variation rate at the plastid genome level, hybridization, and the incidence of biogeography. We conclude that some species-rich tree genera in small geographical regions may prove exceptionally difficult to barcode. Until more efficient markers are developed, we recommend that improved and diversified sampling (multiple locations of sympatric and co-occurring congenerics) be embraced as a timely and important goal for the precise assessment of haplotype specificity to facilitate the productive application of barcoding in practice.
Keywords: DNA barcoding; forest trees; Italy; Quercus; regional sampling

Rapid characterization of dry cured ham produced following different PDOs by proton transfer reaction time of flight mass spectrometry (PTR-ToF-MS). - Del Pulgar, José Sánchez; Soukoulis, Christos; Biasioli, Franco; Cappellin, Luca; García, Carmen; Gasperi, Flavia; Granitto, Pablo; Märk, Tilmann D.; Piasentier, Edi; Schuhfried, Erna (Talanta, 2011)
In the present study, the recently developed proton transfer reaction time of flight mass spectrometry (PTR-ToF-MS) technique was used for the rapid characterization of dry cured hams produced according to 4 of the most important Protected Designations of Origin (PDOs): an Iberian one (Dehesa de Extremadura) and three Italian ones (Prosciutto di San Daniele, Prosciutto di Parma and Prosciutto Toscano). In total, the headspace composition and respective concentration for nine Spanish and 37 Italian dry cured ham samples were analyzed by direct injection without any pre-treatment or pre-concentration. Firstly, we show that the rapid PTR-ToF-MS fingerprinting in conjunction with chemometrics (Principal Components Analysis) indicates a good separation of the dry cured ham samples according to their production process and that it is possible to set up, using data mining methods, classification models with a high success rate in cross validation. Secondly, we exploited the higher mass resolution of the new PTR-ToF-MS, as compared with standard quadrupole based versions, for the identification of the exact sum formula of the mass spectrometric peaks providing analytical information on the observed differences. The work indicates that PTR-ToF-MS can be used as a rapid method for the identification of differences among dry cured hams produced following the indications of different PDOs and that it provides information on some of the major volatile compounds and their link with the implemented manufacturing practices such as rearing system, salting and curing process, manufacturing practices that seem to strongly affect the final volatile organic profile and thus the perceived quality of dry cured ham.
The following values have no corresponding Zotero field: accession-num: 21645714
Keywords: Animals; Data Mining; Dry cured ham; Flavour compounds; Food Handling; Food Handling: methods; Italy; Mass spectrometry; Mass Spectrometry: methods; Meat Products; Meat Products: analysis; PDO; PTR-MS; PTR-ToF-MS; Spain; Swine; volatile compounds; Volatile Organic Compounds

HABITAT USE BY THE EUROPEAN WILD RABBIT (ORYCTOLAGUS CUNICULUS) IN A COASTAL SANDY DUNE ECOSYSTEM OF CENTRAL ITALY - Santilli, Francesco; Bagliacca, Marco (HYSTRIX-ITALIAN JOURNAL OF MAMMALOGY, 2010)
The European wild rabbit (Oryctolagus cuniculus) has been recurrently introduced into Italy since the Roman times. Some populations occur along sandy coastal dunes (Central Italy). There is no information about the ecology and habitat preferences of wild rabbits in this particular ecosystem. During May and June 2009, we assessed the distribution of wild rabbits in a 120 ha protected area (province of Livorno, Tuscany), by faecal pellet counts in 170 circular plots (d = 1 m). Range size defined by Kernel Analysis was 27.3 ha (95%) and 13.2 ha (50%). Habitat selection was assessed through Jacobs' index of selection. Rabbits selected the first dunes that offer both food (psammophilous grasses) and the cover of tamarisk shrubs. Holm oak woods and pinewoods were avoided, probably because of the lack of undergrowth.
Keywords: coastal dunes; habitat selection; Italy; wild rabbit

Fire-vegetation interactions during the Mesolithic-Neolithic transition at Lago dell'Accesa, Tuscany, Italy - Colombaroli, Daniele; Vannière, Boris; Emmanuel, Chapron; Magny, Michel; Tinner, Willy (HOLOCENE, 2008)
A new core from the centre of Lago dell'Accesa (Tuscany, Italy) was sampled for pollen and charcoal analyses to provide a high-resolution sequence from 8400 to 7000 cal. yr BP. We combined series of microscopic charcoal, macroscopic charcoal and pollen to address the response of vegetation to fire at different spatial scales. Before 7900 cal. yr BP, broadleaved evergreen forests of Quercus ilex were the most important vegetational type in the area of Lago dell'Accesa. The subsequent decline of Q. ilex occurred when human-induced fires increased at the Mesolithic/Neolithic transition (c. 8000 cal. yr BP). Cross-correlation analyses show that fire was a key factor for vegetational change. Higher fire incidence affected the forest composition, converting evergreen forests to high-diversity open, partly deciduous forests and shrubby communities. The correlation is more pronounced at a local scale (macroscopic charcoal), whereas at a regional scale (microscopic charcoal) the vegetation followed the fire intervals with a more marked time lag (10-100 years). Climatic change, such as wetter periods inferred from lake levels, may have directly influenced the vegetational change, exacerbating the effect of human impact. Our study suggests that the disruption of evergreen broadleaved forests occurred when mean fire interval reached values as high as those of today's highly disturbed Mediterranean ecosystems. Hence broadleaved evergreen forests may not be as fire-resilient as assumed according to modern ecological paradigms. In view of the projected increase in fire frequency as a consequence of global warming, the present relict forests of Quercus ilex will be strongly affected.
Keywords: climate change; Fire ecology; Fire history; Holocene; Italy; macroscopic charcoal; Mediterranean vegetation; mesolithic; microscopic charcoal; Neolithic; Quercus ilex; tuscany

Fire-vegetation interactions during the Mesolithic-Neolithic transition at Lago dell'Accesa, Tuscany, Italy - Colombaroli, Daniele; Vannière, Boris; Emmanuel, Chapron; Magny, Michel; Tinner, Willy (HOLOCENE, 2008)
A new core from the centre of Lago dell'Accesa (Tuscany, Italy) was sampled for pollen and charcoal analyses to provide a high-resolution sequence from 8400 to 7000 cal. yr BP. We combined series of microscopic charcoal, macroscopic charcoal and pollen to address the response of vegetation to fire at different spatial scales. Before 7900 cal. yr BP, broadleaved evergreen forests of Quercus ilex were the most important vegetational type in the area of Lago dell'Accesa. The subsequent decline of Q. ilex occurred when human-induced fires increased at the Mesolithic/Neolithic transition (c. 8000 cal. yr BP). Cross-correlation analyses show that fire was a key factor for vegetational change. Higher fire incidence affected the forest composition, converting evergreen forests to high-diversity open, partly deciduous forests and shrubby communities. The correlation is more pronounced at a local scale (macroscopic charcoal), whereas at a regional scale (microscopic charcoal) the vegetation followed the fire intervals with a more marked time lag (10-100 years). Climatic change, such as wetter periods inferred from lake levels, may have directly influenced the vegetational change, exacerbating the effect of human impact. Our study suggests that the disruption of evergreen broadleaved forests occurred when mean fire interval reached values as high as those of today's highly disturbed Mediterranean ecosystems. Hence broadleaved evergreen forests may not be as fire-resilient as assumed according to modern ecological paradigms. In view of the projected increase in fire frequency as a consequence of global warming, the present relict forests of Quercus ilex will be strongly affected.
The following values have no corresponding Zotero field: pub-location: 1 OLIVERS YARD, 55 CITY ROAD, LONDON EC1Y 1SP, ENGLAND publisher: SAGE PUBLICATIONS LTD
Keywords: climate change; Fire ecology; Fire history; Holocene; Italy; macroscopic charcoal; Mediterranean vegetation; mesolithic; microscopic charcoal; Neolithic; Quercus ilex; tuscany

Leaf accumulation of trace elements and polycyclic aromatic hydrocarbons (PAHs) in Quercus ilex L. - De Nicola, F; Maisto, G; Prati, M V; Alfani, a (Environmental pollution (Barking, Essex : 1987), 2008)
Quercus ilex L. leaves were collected four times in one year at six urban sites and one remote area in order to determine trace element and PAH accumulation through concomitant analyses of unwashed and water-washed leaves. Both unwashed and washed leaves showed the highest amounts of trace elements and PAHs in the urban area. Unwashed leaves showed greater differences between urban and remote areas and among the urban sites than washed leaves for trace element and PAH concentrations. Water-washing resulted in a significant (P<0.001) decrease in leaf concentrations of Cr, Cu, Fe, Pb, V and Zn. By contrast, Cd and total PAH concentrations showed no differences between unwashed and washed leaves.
Keywords: Air Pollutants; Air Pollutants: analysis; Aromatic; Aromatic: analysis; Atomic; biomonitoring; cadmium; Cadmium: analysis; chromium; Chromium: analysis; Cities; copper; Copper: analysis; Environmental Monitoring; Environmental Monitoring: methods; Iron; Iron: analysis; Italy; lead; Lead: analysis; PAHs; Plant Leaves; Plant Leaves: chemistry; Polycyclic Hydrocarbons; Quercus; Quercus ilex L.; Spectrophotometry; Trace Elements; Trace Elements: analysis; Unwashed and washed leaves; Vanadium; Vanadium: analysis; Zinc; Zinc: analysis

Leaf accumulation of trace elements and polycyclic aromatic hydrocarbons (PAHs) in Quercus ilex L. - De Nicola, F.; Maisto, G.; Prati, M. V.; Alfani, A. (Environmental pollution (Barking, Essex : 1987), 2008)
Quercus ilex L. leaves were collected four times in one year at six urban sites and one remote area in order to determine trace element and PAH accumulation through concomitant analyses of unwashed and water-washed leaves. Both unwashed and washed leaves showed the highest amounts of trace elements and PAHs in the urban area. Unwashed leaves showed greater differences between urban and remote areas and among the urban sites than washed leaves for trace element and PAH concentrations. Water-washing resulted in a significant (P<0.001) decrease in leaf concentrations of Cr, Cu, Fe, Pb, V and Zn. By contrast, Cd and total PAH concentrations showed no differences between unwashed and washed leaves.
The following values have no corresponding Zotero field: accession-num: 17892907
Keywords: Air Pollutants; Air Pollutants: analysis; Aromatic; Aromatic: analysis; Atomic; biomonitoring; cadmium; Cadmium: analysis; chromium; Chromium: analysis; Cities; copper; Copper: analysis; Environmental Monitoring; Environmental Monitoring: methods; Iron; Iron: analysis; Italy; lead; Lead: analysis; PAHs; Plant Leaves; Plant Leaves: chemistry; Polycyclic Hydrocarbons; Quercus; Quercus ilex L.; Spectrophotometry; Trace Elements; Trace Elements: analysis; Unwashed and washed leaves; Vanadium; Vanadium: analysis; Zinc; Zinc: analysis

An application case of ecological indicator values (Zeigerwerte) calculated with a simple algorithmic approach - Fanelli, G.; Pignatti, S.; Testi, A. (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2007)
Abstract The vegetation of the study site near Rome (Castelporziano Estate), where different woodland types occur, was analysed on the basis of ecological indicator values (Zeigerwerte) for light, temperature, continentality of climate, soil moisture, soil pH and nitrogen. Indicator values were estimated with Hill's reprediction algorithm for the flora of Central-Southern Italy relying on a database of 4,207 original relevés representing a balanced survey of the vegetation of this and surrounding areas. It was possible to obtain indicator values for an important fraction of the Italian Mediterranean flora. Results are ecologically reasonable, and it was possible to find strong correlation between the recalculated values and a few environmental variables. These correlations were not significant in an analogous test with subjectively derived scores of Ellenberg indicator values.
From Duplicate 1 (An application case of ecological indicator values (Zeigerwerte) calculated with a simple algorithmic approach - Fanelli, G; Pignatti, S; Testi, A)
Keywords: correlation; Italy; reprediction algorithm; vegetation ecology

An application case of ecological indicator values (Zeigerwerte) calculated with a simple algorithmic approach - Fanelli, G.; Pignatti, S.; Testi, a (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2007)
Abstract The vegetation of the study site near Rome (Castelporziano Estate), where different woodland types occur, was analysed on the basis of ecological indicator values (Zeigerwerte) for light, temperature, continentality of climate, soil moisture, soil pH and nitrogen. Indicator values were estimated with Hill's reprediction algorithm for the flora of Central-Southern Italy relying on a database of 4,207 original relevés representing a balanced survey of the vegetation of this and surrounding areas. It was possible to obtain indicator values for an important fraction of the Italian Mediterranean flora. Results are ecologically reasonable, and it was possible to find strong correlation between the recalculated values and a few environmental variables. These correlations were not significant in an analogous test with subjectively derived scores of Ellenberg indicator values.
From Duplicate 1 (An application case of ecological indicator values (Zeigerwerte) calculated with a simple algorithmic approach - Fanelli, G; Pignatti, S; Testi, A)From Duplicate 1 (An application case of ecological indicator values (Zeigerwerte) calculated with a simple algorithmic approach - Fanelli, G; Pignatti, S; Testi, A)The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: correlation; Italy; reprediction algorithm; vegetation ecology

Folk phytotherapeutical plants from Maratea area (Basilicata, Italy). - Guarrera, Paolo Maria; Salerno, Giovanni; Caneva, Giulia (Journal of ethnopharmacology, 2005)
Field ethnobotanical survey was undertaken for the period of 2002-2003 in the Tyrrhenian part of the Basilicata region of southern Italy. Data of 56 species of plants belonging to 29 families where gathered through interviews; among the species, 47 are used in human therapy, 6 as insect repellents, 15 in veterinary medicine, 1 for its ichthyotoxic properties and 3 for magic therapeutic purposes. The most important findings in ethnomedicine relate to Nasturtium officinale (renal colic, liver diseases), Foeniculum vulgare subsp. piperitum (mouth ulcers), Leopoldia comosa (toothache, headache), Micromeria graeca subsp. graeca (coughs) and Ceterach officinarum (malaria), while in the ethnoveterinary field, we have Pteridium aquilinum (wolf bites) and Spartium junceum (fractures of animal limbs).
Keywords: Abdominal Pain; Abdominal Pain: drug therapy; Anthelmintics; Anthelmintics: therapeutic use; Antiparasitic plants; Basilicata; Common Cold; Common Cold: drug therapy; Cough; Cough: drug therapy; Diuretics; Diuretics: chemistry; Diuretics: therapeutic use; Ethnobotany; Ethnopharmacology; Ethnopharmacology: methods; Furunculosis; Furunculosis: drug therapy; Geography; Humans; Italy; Lung Diseases; Lung Diseases: drug therapy; Medicinal; Medicinal plants; Medicinal: classification; Medicine; Phytotherapy; Plant Preparations; Plant Preparations: therapeutic use; Plants; Skin Diseases; Skin Diseases: drug therapy; Time Factors; Traditional; Veterinary plants; Wound Healing; Wound Healing: drug effects; Wounds and Injuries; Wounds and Injuries: drug therapy

Palaeovegetation from a Homo neanderthalensis occupation in Western Liguria: archaeopalynology of Madonna dell'Arma (San Remo, Italy) - Kaniewski, D; Renault-Miskovsky, J; de Lumley, H (JOURNAL OF ARCHAEOLOGICAL SCIENCE, 2005)
This study presents a short local vegetation history of Western Liguria (San Remo), northwest Italy, based on a palynological analyses of an 8.30-m-long archaeological section in the dune covering Madonna dell'Arma cave. Madonna dell'Arma is one of the Mousterian caves currently located on the Ligurian coastal zone. The site contains Levallois-type Mousterian tools, four pieces of skull attributed to Homo neanderthalensis and fauna remains belonging to Rhinoceros mercki, Elephas sp. and Hippopotamus amphibius. This study is of interest as the site is situated in an area where data on palaeovegetation. are scarce. In fact, the archaeopollen analyses of Madonna dell'Arma cave's surroundings provide a rare local picture of vegetation during the beginning of OIS 4, posterior to 73,100 yr BP. The palynological taxa are grouped into three vegetation units by PCA (principal components analysis). These data suggest a huge Mediterranean pre-steppic forest (Pinus, Quercus ilex and several herbs) colonizing the area during this substage. The adjacent valleys were colonized by a caducifoliate-alluvial forest and Mediterranean scrub vegetation. These vegetation characteristics suggest a semi-arid coastal climate with an increase of precipitation according to altitude. The PCA analyses of the palynological sections inside and outside the cave suggest a nearly continuous vegetation succession from OIS 5a to OIS 4. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: archaeopalynology; Italy; Liguria; Middle Palaeolithic; OIS 4; PCA

Temporal variations in PAH concentrations in Quercus ilex L. (holm oak) leaves in an urban area. - De Nicola, Flavia; Maisto, Giulia; Prati, Maria Vittoria; Alfani, Anna (Chemosphere, 2005)
Temporal variations of polycyclic aromatic hydrocarbon (PAH) concentrations in leaves of a Mediterranean evergreen oak, Quercus ilex L., were investigated in order to assess the suitability of this species to biomonitor PAH air contamination. Leaf samples were collected at six sites of the urban area of Naples (Italy) and at a control site in the Vesuvius National Park, in May and September 2001, and in January and May 2002. PAH extraction was conducted by sonication in dichloromethane-acetone and quantification by GC-MS. In winter, leaf total PAH concentrations showed, at all the urban sites, values 2-fold higher than in all the other samplings, reflecting the temporal trend reported for PAH air contamination in the Naples urban area. Moreover, leaf PAH concentrations showed, at all the urban sites, a decrease in May 2002 after the winter accumulation. At the control site leaf PAH concentrations showed lower values and smaller temporal variations than at the urban sites. The findings support the suitability of Q. ilex leaves to monitor temporal variations in PAH contamination. The highest winter concentrations of total PAHs were due to the medium molecular weight PAHs that increased with respect to both low and high molecular weight PAHs. The medium molecular weight PAHs showed the same temporal trend both at the urban and remote sites.
The following values have no corresponding Zotero field: accession-num: 16182861
Keywords: Aromatic; Aromatic: analysis; Cities; Environmental Monitoring; Environmental Pollutants; Environmental Pollutants: analysis; Italy; Mediterranean evergreen oak; Naples (Italy); PAH biomonitoring; pah leaf accumulation; Plant Leaves; Plant Leaves: chemistry; Polycyclic Hydrocarbons; Quercus; Quercus: chemistry; Seasonal trend; Seasons; Time Factors

Temporal variations in PAH concentrations in Quercus ilex L. (holm oak) leaves in an urban area. - De Nicola, Flavia; Maisto, Giulia; Prati, Maria Vittoria; Alfani, Anna (Chemosphere, 2005)
Temporal variations of polycyclic aromatic hydrocarbon (PAH) concentrations in leaves of a Mediterranean evergreen oak, Quercus ilex L., were investigated in order to assess the suitability of this species to biomonitor PAH air contamination. Leaf samples were collected at six sites of the urban area of Naples (Italy) and at a control site in the Vesuvius National Park, in May and September 2001, and in January and May 2002. PAH extraction was conducted by sonication in dichloromethane-acetone and quantification by GC-MS. In winter, leaf total PAH concentrations showed, at all the urban sites, values 2-fold higher than in all the other samplings, reflecting the temporal trend reported for PAH air contamination in the Naples urban area. Moreover, leaf PAH concentrations showed, at all the urban sites, a decrease in May 2002 after the winter accumulation. At the control site leaf PAH concentrations showed lower values and smaller temporal variations than at the urban sites. The findings support the suitability of Q. ilex leaves to monitor temporal variations in PAH contamination. The highest winter concentrations of total PAHs were due to the medium molecular weight PAHs that increased with respect to both low and high molecular weight PAHs. The medium molecular weight PAHs showed the same temporal trend both at the urban and remote sites.
Keywords: Aromatic; Aromatic: analysis; Cities; Environmental Monitoring; Environmental Pollutants; Environmental Pollutants: analysis; Italy; Mediterranean evergreen oak; Naples (Italy); PAH biomonitoring; pah leaf accumulation; Plant Leaves; Plant Leaves: chemistry; Polycyclic Hydrocarbons; Quercus; Quercus: chemistry; Seasonal trend; Seasons; Time Factors

Ethnopharmacology of ogliastra (villagrande strisaili, sardinia, Italy). - Loi, M. C.; Poli, F.; Sacchetti, G.; Selenu, M. B.; Ballero, M. (Fitoterapia, 2004)
The use of medicinal and aromatic plants was investigated in a group of 200 elderly people (60-104-year-old) from Villagrande Strisaili (Ogliastra, Sardinia, Italy), recording the use of 78 species for the treatment of various ailments, especially of the respiratory tract, the mouth, and the skin. Seventeen plants had never been described as medicinal species in peninsular Italy, while a few others turn out to have an original use for Sardinia.
The following values have no corresponding Zotero field: accession-num: 15158984
Keywords: Italy; Medicinal plants; ogliastra; Sardinia; Traditional phytotherapy; Villagrande Strisaili

Comparative study of Spanish and Italian terrestrial small mammal coenoses from different biotopes in Mediterranean peninsular tip regions - Cagnin, M; Moreno, S; Aloise, G; Garofalo, G; Villafuerte, R; Gaona, P; Cristaldi, M (Journal of Biogeography, 1998)
A comparison of terrestrial small mammal coenoses belonging to nine different biotopes in the tips of the Iberian and Italian peninsulas was carried out using the pitfall trapping method. The influence of both habitat type and peninsular effect on composition of small mammal coenoses was analysed. In Southern Italy, 203 specimens belonging to seven species were trapped: Suncus etruscus (Savi, 1822), Crocidura suaveolens (Pallas, 1811), C. leucodon (Hermann, 1780), Microtus savii (de Sélys-Longchamps, 1838), Apodemus sylvaticus (L., 1758), A. flavicollis (Melchior, 1834) and Mus musculus domesticus Schwarz & Schwarz, 1943. In Southern Spain 428 specimens belonging to five species were trapped: Suncus etruscus, Crocidura russula (Hermann, 1780), Microtus duodecimcostatus (de Sélys-Longchamps, 1839), Apodemus sylvaticus and Mus spretus Lataste, 1883. The relative density of small mammals occurring in the nine Spanish sampling stations was twice that recorded in the Italian stations; however the number of species recorded in the different biotopes show similar mean values, ranging from three to five in Andalusia and from three to six in Calabria. Apodemus sylvaticus was the dominant species in the Calabrian stations, whereas Crocidura russula prevailed in Andalusia. The biotic diversity values are very similar in the Calabrian and Andalusian biotopes. By contrast, the Insectivora/Rodentia ratio was always higher in Andalusia. The more xerophytic biotopes showed greater similarities between the communities in Southern Spain and Southern Italy, while the cooler biotopes differed between these two peninsulas.
Keywords: habitat type; Italy; peninsular effect; sclerophyll biome; Small mammal communities; Spain

Comparative study of Spanish and Italian terrestrial small mammal coenoses from different biotopes in Mediterranean peninsular tip regions - Cagnin, M.; Moreno, S.; Aloise, G.; Garofalo, G.; Villafuerte, R.; Gaona, P.; Cristaldi, M. (Journal of Biogeography, 1998)
A comparison of terrestrial small mammal coenoses belonging to nine different biotopes in the tips of the Iberian and Italian peninsulas was carried out using the pitfall trapping method. The influence of both habitat type and peninsular effect on composition of small mammal coenoses was analysed. In Southern Italy, 203 specimens belonging to seven species were trapped: Suncus etruscus (Savi, 1822), Crocidura suaveolens (Pallas, 1811), C. leucodon (Hermann, 1780), Microtus savii (de Sélys-Longchamps, 1838), Apodemus sylvaticus (L., 1758), A. flavicollis (Melchior, 1834) and Mus musculus domesticus Schwarz & Schwarz, 1943. In Southern Spain 428 specimens belonging to five species were trapped: Suncus etruscus, Crocidura russula (Hermann, 1780), Microtus duodecimcostatus (de Sélys-Longchamps, 1839), Apodemus sylvaticus and Mus spretus Lataste, 1883. The relative density of small mammals occurring in the nine Spanish sampling stations was twice that recorded in the Italian stations; however the number of species recorded in the different biotopes show similar mean values, ranging from three to five in Andalusia and from three to six in Calabria. Apodemus sylvaticus was the dominant species in the Calabrian stations, whereas Crocidura russula prevailed in Andalusia. The biotic diversity values are very similar in the Calabrian and Andalusian biotopes. By contrast, the Insectivora/Rodentia ratio was always higher in Andalusia. The more xerophytic biotopes showed greater similarities between the communities in Southern Spain and Southern Italy, while the cooler biotopes differed between these two peninsulas.
The following values have no corresponding Zotero field: publisher: Blackwell Science Ltd
Keywords: habitat type; Italy; peninsular effect; sclerophyll biome; Small mammal communities; Spain

Two vegetation maps of the same island: floristic units versus structural units - Lux, Andrea; Bemmerlein-Lux, Florian A (Applied Vegetation Science, 1998)
Abstract. This paper presents a comparison of two alternative methods to describe and map vegetation: on the basis of plant species and growth forms, respectively. A stratified random sampling was taken from spontaneous vegetation in 1989 on the volcanic island of Pantelleria (near Sicily, Italy). Cartographic and other comparisons of the results from classification and ordination analysis suggest that the major differences were associated with differences in the time scale of the underlying processes. Species results (leading to floristic vegetation units) were representative of longer-term processes, growth-form results (leading to structural vegetation units) with shorter-term processes. Further implications of these results are discussed.
Keywords: dynamics; fire; growth form; Italy; Pantelleria; structure; succession; Temporal scale

DYNAMIC STAGES IN EXTRAZONAL COENOSIS OF QUERCUS-ILEX IN ABRUZZO (CENTRAL ITALY) - CORBETTA, F; PIRONE, G (RESPONSES OF FOREST ECOSYSTEMS TO ENVIRONMENTAL CHANGES, 1992)
This note has as its objective the study of extrazonal communities of Quercus ilex, found in the inner valleys of Abruzzo (Central Italy) and of the coenosis of substitution dynamically linked to them: Some valleys in the mountains of Abruzzo, and particularly those at Sulmona and Capestrano, to which this research refers, represent, from a climatic point of view, small bounded areas which are thermically high and which interrupt the continuity of the line of low temperatures which characterize the ridge of the Apennines. Other features of these inner areas (whose bottom is about 300–400 m) are the high annual temperature range of about 18°–20°C, and the quite low rate of rainfall (often below 700mm; below 500mm at Capestrano) because of the mountains which stop the wet winds.
Keywords: APS; climate; extrazonal comunities; Italy; Quercus ilex